Analisis Penerapan PSAK 109 Tentang Akuntansi Zakat, Infaq, Sedekah Pada BAZNAS kota Magelang - Bagus Satria Maulana; Muhammad Wahyudi (CV. ITTC INDONESIA, 2026)
This research seeks to examine the application of PSAK 109 related to the accounting of zakat, infaq, and sedekah at BAZNAS Magelang city. The information utilized in this study includes both primary data and secondary data. Data gathering method in this research involved interviews, observations, and documentation. This study employs a qualitative method utilizing a case study approach. The findings of this research show that the application of PSAK 109 concerning recognition, measurement, reporting, and disclosure by BAZNAS of Magelang City has not been entirely aligned with PSAK 109; consequently, initiatives are required to enhance the implementation of PSAK 109 in the financial management of BAZNAS of Magelang City.